The impact of taxation structure on growth: Empirical evidence from EU27 member states - Giuseppe Piroli; Jörg Peschner (Economics and Econometrics Research Institute (EERI), 2023)
What is the impact of taxation on growth? Is it supported by specific taxes and harmed by others? We use an error correction model to study the relationship between the tax composition and GDP growth in the EU27 Member States over the period 1995-2019. Under the constraint of revenue-neutrality, we find that, in the long-run, shifting tax away from labour (personal income tax) is growth-enhancing. In addition, growth is positively associated with a higher share of corporate income tax and consumption taxes in the total tax mix. However, evidence for property taxation is contrary to our expectation. We find a negative link between the share of property taxes and growth. Expectedly, increasing the overall tax burden has a negative impact on growth in the long-run. Results are robust to different model specifications. Supplementary evidence based on a computable general equilibrium model confirms that de-taxing wages for employees and lowering labour costs for employers would push output.
Keywords: H2; O47; C23; C68; 330; EU27; growth; tax mix; personal income tax; corporate income tax; consumptiontaxes; environmental taxes; property taxes; labour tax shift; Computable General Equilibriummodel